Stream surface reconstruction of aero engine blade based on limited measured points. (May 2019) - Yu, Hongying; Lyu, Xuegeng; Liu, Peng
Highlights: Based on the development of the surface reconstruction module of the aero-engine Blade Adaptive Machining System (BAMS), a new method is proposed for reconstructing the blade stream surface, which takes full account of the unique fluid characteristics of the blade and is different from the traditional surface reconstruction method. Different from the usual non-contact point-cloud for surface reconstruction, the velocity field of blade surface is constructed on the basis of contact measured points, laying a foundation for the reconstruction of stream surface. Combining quaternion and its geometric meaning, a subdivision method of blade surface velocity field is proposed to improve the reconstruction accuracy of stream surface. An integral algorithm of stream surface based on subdivision of velocity field and numerical calculation process are presented. Reconstruction example and CFD simulation verify the feasibility and advancement of the proposed method. Abstract: Engine blade is a kind of functional part with surface and fluid characteristics. The blade machining often suffers from low efficiency and poor accuracy. Establishment of the Blade Adaptive Machining System (BAMS) is the trend of blade processing. In the process of adaptive machining, blade surface reconstruction is one of the most important steps. The current method of surface reconstruction is mostly carried out through point-cloud, or the interpolation of spline curves and surfaces, which does not take into account the fluid characteristics of the surface. In view of this, based on the characteristics of blade surface, the method of reconstructing the blade stream surface is studied. Combined with the contact measured points and quaternion spherical interpolation method, a method of constructing the velocity field is proposed. On this basis, the subdivision method of velocity field and the integral algorithm are put forward to improve the reconstruction accuracy. Stream surface reconstruction example and computational fluid mechanics (CFD) simulation show that the reconstructed stream surface has better fluid characteristics than that of the surface reconstructed by the spline curve interpolation, which shows the effectiveness and advancement of the proposed method. The research also provides some technical support for the reverse engineering occasions of surface reconstruction of these parts with fluid functional characteristics.